Influence of Fluoropolymer Film Modified With Nanoscale Photoluminophor on Growth and Development of Plants - Ivanyuk, Veronika V.; Shkirin, Alexey V.; Belosludtsev, Konstantin N.; Dubinin, Mikhail V.; Kozlov, Valeriy A.; Bunkin, Nikolay F.; Dorokhov, Aleksey S.; Gudkov, Sergey V. (Frontiers in Physics, 2020)
The red and blue ranges of the optical spectrum are most suitable for plant photosynthesis. Moreover, quanta of red light stimulate photosynthesis more than quanta of blue light. In northern latitudes, the average daily intensity of the red and blue parts of the spectrum is usually not sufficient for many plants. To increase the productivity of greenhouses in northern latitudes, a technology has been developed for fluoropolymer films with photoconversion nanoparticles (quantum dots) that convert UV radiation and violet light into red light. The use of photoconversion fluoropolymer films promotes an increase in the biomass of plants grown in greenhouses at high latitudes. The greatest effect is observed when tomato plants are grown under photoconversion fluoropolymer films. The biomass of tomato berry obtained from one bush grown under films is 20% higher than the biomass of berry of control tomato plants.